Nitric Acid Trihydrate (NAT) in Polar Stratospheric Clouds - Voigt, Christiane; Schreiner, Jochen; Kohlmann, Andreas; Zink, Peter; Mauersberger, Konrad; Larsen, Niels; Deshler, Terry; Kröger, Chris; Rosen, Jim; Adriani, Alberto; Cairo, Francesco; Donfrancesco, Guido Di; et al. (Science, 2000)
International audience A comprehensive investigation of polar stratospheric clouds was performed on 25 January 2000 with instruments onboard a balloon gondola flown from Kiruna, Sweden. Cloud layers were repeatedly encountered at altitudes between 20 and 24 kilometers over a wide range of atmospheric temperatures (185 to 197 kelvin). Particle composition analysis showed that a large fraction of the cloud layers was composed of nitric acid trihydrate (NAT) particles, containing water and nitric acid at a molar ratio of 3:1; this confirmed that these long-sought solid crystals exist well above ice formation temperatures. The presence of NAT particles enhances the potential for chlorine activation with subsequent ozone destruction in polar regions, particularly in early and late winter.